A Conceptual Approach to Education for Social and Environmental Justice - Sergio Carneros; F. Javier Murillo; Irene Moreno-Medina (Universidad Autónoma de Madrid, 2018)
Social Justice and Environmental Justice are two strongly intertwined approaches that can be considered only one. In this paper, we address the conceptualization of the term of Social and Environmental Justice, as a whole, based on the review of four main concepts about it and that coexist today: Social and Environmental Justice as Distribution, from the Theory of Capacities, such as Recognition and Participation. Based on these ideas, Social and Environmental Justice is considered as the achievement of the recognition, participation and distribution of material, cultural and environmental resources (both harmful and beneficial) in a full and equitable manner, all under a criterion intragenerational, intergenerational, interspecies and international that allows the development of a dignified life. This concept develops an idea of Education for Social and Environmental Justice which is multidimensional and it's made from four elements: Equitable education, critic education, democratic education and education for sustainable (or environmental) development.